THE TRANSITION OF ADOLESCENTS TO ADULT NEPHROLOGY CARE: A SURVEY ON YOUNG ADULTS' EXPERIENCE - (:unkn) unknown (ISTANBUL UNIV, FAC MEDICINE, PUBL OFF, 2021)
Objective: As increasing number of young people with renal diseases are reaching adulthood and issues related to their transition to adult units are getting more important. Failure to transfer adolescents under a well-designed transfer program can lead to a decline in attendance to an adult unit. We aim to share our experience and the views of the patients who went through a transition program. Material and Methods: We conducted a telephone questionnaire with 88 patients, who were asked to evaluate their concerns before their transition and their experience during the visit in the adult nephrology unit after the transition process. Results: The mean age of participants was 19.21 +/- 0.97 years. Thirty patients (34%) had chronic kidney disease, and three of them were on dialysis. Three patients (3.4%) had a renal transplant at the time of transition. Fifty-one patients (58%) were felt anxious before the transition process. After their transfer to the adult unit, although 84 patients (95.5%) were satisfied to be in the adult unit, there were still 65 patients (74%) ready to return to the pediatric unit, if it was possible. Conclusion: Transition to the adult unit is still a cause of concern for adolescent patients, even if they are transferred under a well-designed program. It is important to raise awareness about transition programs among pediatricians and to develop a pediatric-adult transition program for the medical and psychological well-being of patients.
Keywords: Adolescence; pediatrics; questionnaire; transition; SERVICES